The AGES-Reykjavík Study: The Prevalence of Amnestic MCI in an Elderly Population - Vin Þorsteinsdóttir 1973- (2009)
Amnestic MCI (aMCI) has been consistently singled out as an important risk factor for Alzheimer´s dementia but few studies have investigated the multidomain amnestic subtype of MCI. The purpose of this study was first to estimate the prevalence of the two amnestic MCI subtypes, single domain and multidomain and second, to examine the associations of age, gender and education level with singleand multidomain amnestic MCI. A community sample of 2135 non-demented individuals aged 66 to 92 years, who participated in the AGES-Reykjavík longitudinal study, was examined. Standard scores for a battery of neuropsychological tests were calculated and participants who did not complete all tests or answer all relevant questions were removed from the sample, leaving 1557 participants. Criteria for amnestic MCI subtypes according to Winblad et al. (2004) were applied. Total amnestic MCI prevalence was estimated 13.8% and the prevalence of the subtypes single domain amnestic MCI and multidomain amnestic MCI was identical, at 6.9%. Amnestic MCI increased with age and men had a greater overall risk ratio, 1.3, of having aMCI, compared to women. Men between 66 and 69 years had a risk ratio of 6.9 for having single domain amnestic MCI compared to women in the same age group. Men under the age of 75 had a risk ratio of 2.1 of having single domain amnestic MCI, compared to women, whereas, among subjects 75 and older, there was no significant gender difference. Multidomain aMCI increased with age in a curvilinear fashion, but no relation to gender was observed. No direct relations of aMCI subtypes with education were observed but an interaction between education and aMCI subtypes was found, indicating that subjects with higher level of education tend to develop aMCI later in life, the difference being larger for multidomain type than single domain type. No other studies have reported such a large gender ix difference in any type of MCI, although some studies do report greater male prevalence of aMCI. An age-gender interaction on the ...